(untitled) (Swiss Medical Weekly, 2012)
Chronic kidney disease (CKD) represents a relevant medical and financial burden. More than 5% of the population suffers from CKD. There should be an accurately timed evaluation of best renal replacement therapy in all patients with CKD. Kidney transplantation is the treatment of choice for patients with end-stage renal disease. Living donated kidney transplantation offers the best results and should be evaluated in every patient suitable for transplantation. Haemodialysis and peritoneal dialysis are equally effective treatment options in patients not suitable for transplantation and should be individually evaluated. Conservative treatment, avoiding a dialysis treatment, can also be an option. Close cooperation of the general practitioner with a nephrologist improves patient management and helps to lower costs. Summary and conclusions There should be an accurately timed evaluation of best renal replacement therapy in all patients with CKD. However conservative treatment can also be an option. Kidney transplantation is the treatment of choice for patients with end-stage renal disease. Living donated kidney transplantation offers the best results and should be evaluated in every patient suitable for transplantation. Haemodialysis and peritoneal dialysis are equally effective treatment options in patients not suitable for transplantation or to bridge time to transplantation and should be individually evaluated. Close cooperation of the general practitioner with a nephrologist improves patient management and helps to lower costs.